Design space analysis of an autonomous aerial crane VTOL concept with a detachable airship envelope - Ito, Y. (My University, 2018)
This paper will argue the concept of a logistics autonomous aerial crane type VTOL aircraft capable of being able to optionally attach an airship envelope so that it will contribute to the reduction of the total weight of the aircraft and requires less energy consumption for flight. In order to overcome the disadvantages or airships those are; first the difficulty of operation in gusty condition, and second its massive size of envelope when to rely fully the weight to be afloat solely by the floating gas, this concept is to attach a medium size flotation envelope to save the energy required for the craft to be airborne which will be only used when the weather is mild, and make the powertrain flyable either with or without the airship component. In order to pursuit the reality of this idea, this study will focus on three major issues: the design on the lifting and propulsion system, method to keep the shape of the envelope in health regardless of traveling in speed or under side winds while on ground, and discussion on the weather condition to become the boundary of the usability of the auxiliary airship.